Extracellular vesicles and systemic lupus erythromatosus - Rasha N Omran; Emad M El Shebini; Enas S Zahran; Sabry A Shoeib (SpringerOpen, 2019)
Introduction Extracellular vesicles (EV) have emerged as important 'nanoshuttles' of information between cells, carrying proteins, genetic information, and bioactive lipids to modify the phenotype and function of recipient cells. EVs are potential regulators in autoimmune disorders, playing a determinant role in the appearance and maintenance of inflammation. Objective This study aimed to carry out an up-to-date review of the EVs and their relationship with systemic lupus erythromatosus. Data sources Medline databases (PubMed, Medscape, ScienceDirect, EMF-Portal) and all materials available in the Internet till 2018. Study selection This search yielded 275 articles. The articles were studied to perform an up-to-date review of the extracellular vesicles and their relationship with systemic lupus erythromatosus. Data extraction If the studies did not fulfill the inclusion criteria, they were excluded. Study quality assessment included whether ethical approval was obtained, the eligibility criteria specified, appropriate controls, and adequate information and defined assessment measures. Data synthesis Comparisons were made by a structured review, with the results tabulated. Conclusion We can safely conclude that EVs play an important role in the complex pathogenesis and management of systemic lupus erythematosus.